Collaborative Governance dalam Membangun City Branding Sparkling Surabaya: Studi Kasus Layanan Bus Surabaya Sightseeing and City Tour (SSCT) - Satya, Andiyasa Mahardhika; Rahmawati, Ainul Lailatul; Sholikhah, Putri (Economic Reviews Journal, 2025)
This research focuses on collaborative governance. The government is trying to build sparkling city branding in the Surabaya Sightseeing and City Tour (SSCT) bus service which operates in collaboration with Disbudporapar. This research aims to describe the coordination between the Surabaya City Government and Disbudporapar in implementing this program. The type of research used is descriptive qualitative, carried out during data collection and after data collection is complete. This research uses data analysis from Miles and Huberman, namely an interactive model. Based on a qualitative approach, this research uses data collection techniques by means of literature study, observation and interviews. The research focus uses the Collaborative Governance theory according to Ansell and Gash which consists of Face to Face Dialogue, Trust Building, Commitment to The Process, Shared Understanding and Intermediate Outcome.